Modernizing agriculture and fisheries: Overview of issues, trends, and policies - Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2022)
This paper offers an overview toward assessing the implementation of the Agriculture and Fisheries Modernization Act (AFMA) or Republic Act 8435, the country's landmark legislation on the sustainable and equitable development of its agriculture and fisheries. The study presents a Theory of Change implicit in the AFMA, and reviews the Philippines' agricultural development trends, within an overall economic context of structural change. It concludes with a synthesis of past AFMA program reviews.
Keywords: 330; Agricultural development; modernization; technical progress; inclusive growth; smallholders; structural change